2017
DOI: 10.1556/030.64.2017.016
|View full text |Cite
|
Sign up to set email alerts
|

Association between Toxoplasma gondii types and outcomes of human infection: A meta-analysis

Abstract: The virulence and pathogenicity of various types of Toxoplasma gondii differ considerably in mice. Recent studies have claimed that similar phenomenon was observed in humans, but no relevant studies have been performed to validate this finding. In addition, reports showing association between a given T. gondii type and outcomes of human infection yielded conflicting results. To provide a more precise estimation of the association and a more reliable conclusion on this subject, we performed this meta-analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Although there was no relationship between T. gondii infection and AD determined in the present study, we believe that reproduction of the study with other genotypes of T. gondii would be a positive contribution to the literature. Xia et al [31] observed in the study they conducted in 2017 that different T. gondii species demonstrate different virulence levels and cause different results in humans. Studies with a larger sample size investigating various species of T. gondii are required to extend the findings of the current study.…”
Section: Resultsmentioning
confidence: 99%
“…Although there was no relationship between T. gondii infection and AD determined in the present study, we believe that reproduction of the study with other genotypes of T. gondii would be a positive contribution to the literature. Xia et al [31] observed in the study they conducted in 2017 that different T. gondii species demonstrate different virulence levels and cause different results in humans. Studies with a larger sample size investigating various species of T. gondii are required to extend the findings of the current study.…”
Section: Resultsmentioning
confidence: 99%
“…T. gondii exists as many strains, which belong to clonal lineages or present atypical or recombinant genetics; these strains are often distinguished on virulence, defined by rates of migration, invasion, and replication in vitro, and lethal dose 100 in vivo in mice [31]. Both virulent and avirulent strains commonly cause human ocular toxoplasmosis [32]. In keeping, we observed the proliferating phenotype in human retinal pigment epithelial cells exposed to virulent (GT-1) or avirulent (DEG) T. gondii strains.…”
Section: Discussionmentioning
confidence: 99%
“…This reflects not only the ability of T. gondii to evade the immune system and establish a latent infection but also the heterogeneity of T. gondii strains in the clinical population [138]. Strains noticeably differ in virulence, clinical outcomes, and prevalence between regions [139,140]. In North America and Europe, approximately 90% of reported samples can be classified into one of three intercontinental clonal lineages (types I, II, and III) which exhibit approximately 1-2% differences at the nucleotide level [141,142].…”
Section: Toxoplasma Gondiimentioning
confidence: 99%
“…Moreover, a great deal of diversity has arisen in South America as a result of atypical and recombinant strains, and as such clonal lineage prevalence is low [140]. In humans, type II strains (e.g., typified by the isolates Prugniaud and ME49) are strongly associated with infection irrespective of clinical presentation; however, differences in virulence have been suggested due to associations of type I and type III strains with cerebral and pulmonary toxoplasmosis, respectively [139]. The vast diversity between strains exemplifies the need to study T. gondii virulence effectors, how clinical outcomes vary between strains, and increase awareness of prevention strategies in regions with high T. gondii seroprevalence.…”
Section: Toxoplasma Gondiimentioning
confidence: 99%